Matéria orgânica e nutrientes em agroecossistemas sob cultivo orgânico e irrigado - Gadelha, Janine Colares (2015)
The need to understand the workings and dynamics of soil organic matter in areas where this feature is available in high quantities (organ systems) and how this dynamic can be affected by the interaction between the organic matter and the factors that are present in the system as the type of soil, climate, and management used, this study aimed to evaluate the effects of organic matter and nutrients added to the soil via organic compounds, quantifying the same with focus on chemical properties of soil, time and levels of storage of this nutrient, the form of release thereof by the action of irrigation and shade on inputs applied in organic caribean cherry orchards. The research was developed in Amway Nutrilite farm located in Brazil, Ibiapaba region, state of Ceará, from February 2011 to April 2013. Areas with one, six and ten years of organic management were investigated. Inputs and outputs of substances in the culture were measured, the soils were analyzed for nutrient content (N, P, K, Ca, Mg), organic matter (OM), density and chemical properties, electrical conductivity (EC), sum bases exchangeable (SEB), capacity of effective cation exchange (ECEC) at pH 7 (CEC) and base saturation index (IBS). The samples were collected at four depths (0-20; 20-50; 50-100; 100-150 cm) lines and between lines. An experimental part was carried out with the aid of litter boxes made of rectangular form with a base and their lower side mesh 4 mm and the largest side of PVC, and the same mesh cover. Were filled with the compound used in farm and evaluated in seven times (0, 2, 4, 6, 8, 10, 12 months) after assembly, the remaining amounts of the compound were weighed and calculated moisture as well as the amount of nutrients present, decomposition rates and half-life values were calculated. Soil under litter boxes were analyzed before and after the removal of boxes to analyzed nutrients content (N, P, K, Ca, Mg) and organic carbon, at three depths (0 to 5, 5 to 10, 10 to 20 cm). The chemical properties decreased with depth, and the organic carbon and nutrient contents increased with increasing amounts of organic matter and nutrients applied. Only a small percentage of OM applied remained in the soil to 150 cm deep. Much of K, Ca and Mg were not present in the soil and available P (P1) was a minor proportion of P applied. The OM was positively related to the EC, PM1, K, Ca, Mg, SEB, ECEC, CEC, IBS and N. Culture recovered significant part of the K and N applied, but Ca, Mg and P were lost or did not remain in available forms, probably due to leaching (Ca, Mg) and also possibly by removal by insects (Ca, Mg, P). Large deposits OM (up to 300 t ha-1) were added over a period of 10 years, not promoting significant increase in the OM content of any soil horizon, indicating that the microbial decomposition and other losses of OM were added under extensive this management (Chapter 1). The compound decomposed rapidly over time, and faster in central pivot than micro-sprinkler. Total shading caused higher rates of decomposition. The half-life ranged from 0.12 to 1.02 years. The nutrient losses were substantial, P and K being decomposed at faster rates than weight loss. Lost compound nutrients were not mostly in the soil. Insects can be removed compound from the boxes becoming unavailable to plants (Chapter 2). From these results it was found that the intake of large amounts of organic matter to the soil for long periods did not cause the expected effect, but kept the system in balance. It is recommended further studies in the area especially in discerns this fauna, to a better understanding of this dynamic, in the studied conditions.